2003
DOI: 10.1074/jbc.m213128200
|View full text |Cite
|
Sign up to set email alerts
|

A Broken α-Helix in Folded α-Synuclein

Abstract: ␣-Synuclein is a small cytosolic protein of presynaptic nerve terminals composed of seven 11-residue repeats and a hydrophilic tail. ␣-Synuclein misfolding and dysfunction may contribute to the pathogenesis of Parkinson's disease and neurodegenerative dementias, but its normal folding and function are unknown. In solution, ␣-synuclein is natively unstructured but assumes an ␣-helical conformation upon binding to phospholipid membranes. We now show that this conformation of ␣-synuclein consists of two ␣-helical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

36
597
3
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(639 citation statements)
references
References 19 publications
36
597
3
3
Order By: Relevance
“…These repeats are similar to those found in apolipoproteins, and it was proposed that the lipid interaction of ␣-synuclein could be similar to that of the apolipoproteins (8,13). The involvement of the N terminus in membrane interaction was subsequently confirmed experimentally by analysis of ␣-synuclein deletion mutants (15) and NMR studies of liposomebound ␣-synuclein (18)(19)(20). The latter studies revealed an ordering of the N-terminal repeat regions induced upon membrane binding whereas the highly charged C terminus remained unstructured and, therefore, was not involved in membrane interaction.…”
mentioning
confidence: 53%
“…These repeats are similar to those found in apolipoproteins, and it was proposed that the lipid interaction of ␣-synuclein could be similar to that of the apolipoproteins (8,13). The involvement of the N terminus in membrane interaction was subsequently confirmed experimentally by analysis of ␣-synuclein deletion mutants (15) and NMR studies of liposomebound ␣-synuclein (18)(19)(20). The latter studies revealed an ordering of the N-terminal repeat regions induced upon membrane binding whereas the highly charged C terminus remained unstructured and, therefore, was not involved in membrane interaction.…”
mentioning
confidence: 53%
“…2(B)] are consistent both with this conclusion and with conclusions based on 15 N NMR data, which show that the N-terminal region of the protein binds SDS while the C-terminal region remains disordered. 13,20,24,28,31,32 Solution NMR is a powerful tool for accessing processes that occur over a range of timescales. 26 In 250 mM NaCl, SDS forms larger rod-like micelles, decreasing the tumbling rate of the a-synuclein-micelle complex.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23][24][25] The last $40 residues lack defined structure and do not appear to be involved in membrane interactions. 13,21 Recent solution NMR data, however, appear incompatible with this model. More specifically, 15 N intensity and relaxation data from titration of SUVs sugget there exists several binding modes in which the first 25 residues adopt a helical state that anchor the interaction with SUVs.…”
mentioning
confidence: 99%
See 2 more Smart Citations